HUBUNGAN ANTARA NYERI PUNGGUNG BAWAH DENGAN KEGIATAN SEDENTARI PADA SISWA SMPN 9 DEPOK SELAMA PANDEMI COVID 19 - Aulia Noor Pradipta (2021)
When the Covid-19 currently teenangers especially junior high school spend more time in front of gadgets that causes a lack of bring out much energy and can occorrence of disabillities of low back pain. The research aims is to knowing correlation of low back pain with sedentary behavior to studentr=s of SMPN 9 Depok during the Covid-19 pandemic. The method of this research is descriptive corrrelative research with cross sectional design. The parameter used were Adolescent Sedentary Activity Questionnaire (ASAQ) and Numeric Rating Scale (NRS). Data analysys using statistica test. From of the research get results p= 0,000 (<0,05) and the results of the Chi-Square test amounted to 0,335 which existence not correlation of low back pain and sedentary behavior. Keywords: Sedentary Behavior, Low Back Pain, Junir High School Student